Population Pharmacokinetic Modeling and Simulation of TV‐46000: A Long‐Acting Injectable Formulation of Risperidone. Issue 7 (4th March 2022) - Perlstein, Itay; Merenlender Wagner, Avia; Gomeni, Roberto; Lamson, Michael; Harary, Eran; Spiegelstein, Ofer; Kalmanczhelyi, Attila; Tiver, Ryan; Loupe, Pippa; Levi, Micha; Elgart, Anna
Abstract: TV‐46000 is a long‐acting subcutaneous antipsychotic that uses a novel copolymer drug delivery technology in combination with a well‐characterized molecule, risperidone, that is in clinical development as a treatment for schizophrenia. A population pharmacokinetic (PPK) modeling and simulation approach was implemented to identify TV‐46000 doses and dosing schedules for clinical development that would provide the best balance between clinical efficacy and safety. The PPK model was created by applying pharmacokinetic data from a phase 1 study of 97 patients with a diagnosis of schizophrenia or schizoaffective disorder who received either single or repeated doses of TV‐46000. The PPK model was used to characterize the complex release profile of the total active moiety (TAM; the sum of the risperidone and 9‐OH risperidone concentrations) concentration following subcutaneous injections of TV‐46000. The PK profile was best described by a double Weibull function of the in vivo release rate and by a 2‐compartment disposition and elimination model. Simulations were performed to determine TV‐46000 doses and dosing schedules that maintained a median profile of TAM concentrations similar to published TAM exposure following oral risperidone doses that have been correlated to a 40% to 80% dopamine‐D2 receptor occupancy therapeutic window. The simulations showed that therapeutic dose ranges for TV‐46000 are 50 to 125 mg for once‐monthly and 100 to 250 mg for the once every 2 months regimens. This PPK model provided a basis for prediction of patient‐specific exposure and dopamine‐D2 receptor occupancy estimates to support further clinical development and dose selection for the phase 3 studies.